1964
DOI: 10.1055/s-0038-1654834
|View full text |Cite
|
Sign up to set email alerts
|

Surface Factor Mechanisms in Relation to Blood Platelets: Evidence that Activated Hageman Factor is Present on the Surface of Platelets*

Abstract: SummaryBlood platelet suspensions from normal (N) or hemophilia A (VIII-) subjects contain active SF (surface factor or activation product) in their plasmatic atmosphere. Since factor XII is an essential precursor, SF is not formed on platelets from a Hageman-deficient. Experimental evidence establishing these facts was obtained by means of clotting tests (PCa and PTT) and the thrombelastograph (TEG). The SF activity of normal platelets, like a plasma SF preparation, corrects the deficiencies in XII- plasmas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1968
1968
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Factor XII is a positively charged protein [29] which can be adsorbed readily onto the platelet surface [24], thereby increasing platelet electro phoretic mobility. The negative results on platelet eletrophoretic mobility reported by B a n g el al.…”
Section: Discussionmentioning
confidence: 99%
“…Factor XII is a positively charged protein [29] which can be adsorbed readily onto the platelet surface [24], thereby increasing platelet electro phoretic mobility. The negative results on platelet eletrophoretic mobility reported by B a n g el al.…”
Section: Discussionmentioning
confidence: 99%
“…A number of early observations provided in direct clues to a possible contribution of platelets to contact activation. First, washed platelets were ob served to provide coagulant activity 13 originally interpreted as Factor XIa 20,21 and subsequently as Factor XI. 19,58 Second, adenosine diphosphate (ADP) was found to shorten the clotting times of platelet-rich plasma in silicon-coated but not uncoated glass tubes both in vitro 34,39 and in vivo.…”
Section: Contributions Of Platelets To Contact Activationmentioning
confidence: 99%
“…Early studies provided evidence consistently demonstrating the presence of Factor XI-like activ ity in platelet suspensions, although the interpreta tions of these studies differed. 4,13,[19][20][21]28,43,44,55,58 It has been estimated that platelets contain approxi mately 1 to 6 U of Factor XI activity per 10 11 plate lets. 28,55 Both Factor XI coagulant activity and Factor XI antigen have now been demonstrated in washed platelet suspensions, and subcellular frac tionation studies have demonstrated that Factor XI activity is present in the platelet plasma membrane fraction.…”
Section: Factor XImentioning
confidence: 99%
“…10,11 FXII is peripherally associated with the platelet surface, eliciting activation of the intrinsic coagulation pathway in the microenvironment of the cell. 12,13 Although processes involving FXII that occur on the platelet surface are poorly understood, the net effect of the close relationship between FXIIa-mediated coagulation and platelet activation is synergistic for earlier initiation of fibrin polymerization. 10 These two lines of evidence indicate that continuous filament glass might be a valuable component of a haemostatic textile.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activation by biomaterials (e.g., via integrin outside‐in signaling, especially glycoprotein IIb/IIIa) can result in surface presentation of phosphatidylserine, an important component of catalytic complexes for thrombin generation 10, 11. FXII is peripherally associated with the platelet surface, eliciting activation of the intrinsic coagulation pathway in the microenvironment of the cell 12, 13. Although processes involving FXII that occur on the platelet surface are poorly understood, the net effect of the close relationship between FXIIa‐mediated coagulation and platelet activation is synergistic for earlier initiation of fibrin polymerization 10.…”
Section: Introductionmentioning
confidence: 99%